2007
DOI: 10.1097/wno.0b013e31803351bb
|View full text |Cite
|
Sign up to set email alerts
|

Optic Neuropathy Associated With Periostitis in Relapsing Polychondritis

Abstract: Optic neuropathy is an uncommon manifestation of relapsing polychondritis (RPC), a rare systemic disease affecting cartilaginous and proteoglycan-rich structures. The optic neuropathy has been attributed to ischemia, intrinsic inflammation of the optic nerve, or spread of inflammation to the nerve from adjacent intraconal orbital tissues. We report a case of recurrent corticosteroid-responsive optic neuropathy in which MRI did not show ocular, optic nerve, or intraconal orbital abnormalities but did show perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Severe visual impairment is also rare in RP but can be due to ischemic optic neuropathy, optic neuritis, or spread of inflammation to the optic nerve from adjacent orbital tissues . In our case, the inflammation of posterior sclera had most likely spread to the optic nerve, causing severe papilledema and visual impairment.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Severe visual impairment is also rare in RP but can be due to ischemic optic neuropathy, optic neuritis, or spread of inflammation to the optic nerve from adjacent orbital tissues . In our case, the inflammation of posterior sclera had most likely spread to the optic nerve, causing severe papilledema and visual impairment.…”
Section: Discussionmentioning
confidence: 68%
“…1,2 Although scleritis is a common complication, severe visual impairment is also rare in RP. 3 We herein report a case of RP with severe visual impairment and asymptomatic brain inflammatory lesions preceding clinical signs of chondritis.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…175 Associated bilateral disk edema has been reported with the condition, 30,176,177 but no cases of UDE were discovered for this review. Thrombocytopenia Thrombocytopenia (low platelets) has been linked to bilateral disk edema 178 and disk edema in conjunction with other Neonatal onset multisystem inflammatory disease (NOMID) 294,295 Relapsing polychondritis 296 Systemic lupus erythematosus 297,298 Local vasculitides Optic disk edema with macular star (ODeMS) 299,301 Optic disk vasculitis (ODV) 302,304 Sarcoidosis (no optic nerve head granulomas) [9][10][11]311,312 Other biochemical alterations in cells Decreased nitric oxide concentration Hypercholesterolemia 242…”
Section: Changes In O 2 Saturation Low O 2 Availabilitymentioning
confidence: 99%
“…Hirunwiwatkul et al reported that there had been 25 previous reported cases of optic neuropathy (ON) in RPC, 4 cases as ischaemic, 13 as inflammatory and 8 of indeterminate mechanism. They presumed that vision should be improved after anti‐inflammatory treatment in inflammatory ON and not in ischaemic ON.…”
mentioning
confidence: 99%